Velocity Distribution Associated With EUV Disturbances Caused by Eruptive MFR - Mei , Zhixing; Cai , Qiangwei; Ye , Jing; Li , Yan; Zhu , Bojing (Frontiers in Astronomy and Space Sciences, 2021)
Extreme ultraviolet (EUV) disturbances are ubiquitous during eruptive phenomena like solar flare and Coronal Mass Ejection (CME). In this work, we have performed a three-dimensional (3D) magnetohydrodynamic numerical simulation of CME with an analytic magnetic fluxrope (MFR) to study the complex velocity distribution associated with EUV disturbances. When the MFR erupts upward, a fast shock (FS) appears as a 3D dome, followed by outward moving plasma. In the center of the eruptive source region, an expanding CME bubble and a current sheet continuously grow, both of which are filled by inward moving plasma. At the flanks of the CME bubble, a complex velocity distribution forms because of the dynamical interaction between inward and outward plasma, leading to the formation of slow shock (SS) and velocity separatrix (VS). We note two types of vortices near the VS, not mentioned in the preceding EUV disturbance simulations. In first type of vortex, the plasma converges toward the vortex center, and in the second type, the plasma spreads out from the center. The forward modeling method has been used to create the synthetic SDO/AIA images, in which the eruptive MFR and the FS appear as bright structures. Furthermore, we also deduce the plasma velocity field by utilizing the Fourier local correlation tracking method on the synthetic images. However, we do not observe the VS, the SS, and the two types of vortices in this deduced velocity field.